2023
DOI: 10.1002/jimd.12609
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for urea cycle defects: An update from historical perspectives to future prospects

Abstract: Urea cycle defects (UCDs) are severe inherited metabolic diseases with high unmet needs which present a permanent risk of hyperammonaemic decompensation and subsequent acute death or neurological sequelae, when treated with conventional dietetic and medical therapies. Liver transplantation is currently the only curative option, but has the potential to be supplanted by highly effective gene therapy interventions without the attendant need for life‐long immunosuppression or limitations imposed by donor liver su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 113 publications
0
3
0
Order By: Relevance
“…Gene therapy options are rapidly evolving and under active investigation for urea cycle disorders. 60 Our gene editing strategy offers advantages over gene transfer by viral vectors. LNPs present lower immunogenicity compared to viral vectors, circumventing the risk of existing or triggered anti-viral antibodies, and possibly allowing for subsequent applications of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Gene therapy options are rapidly evolving and under active investigation for urea cycle disorders. 60 Our gene editing strategy offers advantages over gene transfer by viral vectors. LNPs present lower immunogenicity compared to viral vectors, circumventing the risk of existing or triggered anti-viral antibodies, and possibly allowing for subsequent applications of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For CPS1 deficiency, the size of CPS1 gene and the limited AAV packaging capacity required a split-approach with two AAV vectors. 25 Nevertheless, in preclinical studies for CPS1 deficiency as well as other urea cycle disorders, AAV have shown phenotype correction with increased survival, improved growth, normalization of ammonia and plasma amino acid concentrations (reviewed by Duff et al 26 ). The preclinical studies in OTC deficiency have led to a first-in-human Phase I/II AAV8 gene therapy clinical trial for adults with late-onset OTC deficiency sponsored by Ultragenyx (NCT02991144), with seven patients considered as responders out of 11 treated.…”
Section: Urea Cycle Disordersmentioning
confidence: 99%
“…9 Duff et al review the specificities, development and perspectives of gene therapy for urea cycle defects. 10 Chandler and Venditti summarise the preclinical studies and clinical trials of genetic therapies developed for methylmalonic and propionic acidaemias and lessons learned over the years. Martinez et al provide an update on proof of concept in animal models and clinical trials of gene therapy for phenylketonuria, including recent innovative preclinical approaches of introducing an acquired competitive advantage of genetically modified hepatocytes.…”
mentioning
confidence: 99%